Paradigms, Schools and Concepts in Building up the Scientific Identity of Strategic Management - Suszyński, Cezary (Studia Oeconomica Posnaniensia, 2019)
This theoretical study aims to give a closer presentation of selected, crucial elements determining the level of the scientific identity of strategic management as the sub-discipline of management sciences. The content and scope of the analysis is demarcated by three research questions concerning the process of changes in the disciplinary matrix (paradigm) of strategic management, development of its leading schools, and an emerging scientific identity of strategic management. Following the retrospective approach the subject, main concepts, and research methods appear to be the leading elements in building up the scientific identity of strategic management. Taking a prospective approach, further development and strengthening of a strategic management identity may continue on a new, broader platform of the natural sciences integrating partial, business and technological paradigms.